They live in the land down under: thyroid function and basal metabolic rate in the Blind Mole Rat, Spalax. (23rd September 2013) - Avivi, Aaron; Nevo, Eviatar; Cohen, Keren; Sotnichenko, Nick; Hercbergs, Aleck; Band, Mark; Davis, Paul J.; Ellis, Martin; Ashur-Fabian, Osnat
Abstract: The Israeli blind subterranean mole rat ( Spalax ehrenbergi superspecies ) lives in sealed underground burrows under extreme, hypoxic conditions. The four Israeli Spalax allospecies have adapted to different climates, the cool–humid ( Spalax galili, 2 n = 52 chromosomes), semihumid ( S. golani, 2 n = 54) north regions, warm–humid ( S. carmeli, 2 n = 58) central region and the warm–dry S. judaei, 2 n = 60) southern regions. A dramatic interspecies decline in basal metabolic rate (BMR) from north to south, even after years of captivity, indicates a genetic basis for this BMR trait. We examined the possibility that the genetically-conditioned interspecies BMR difference was expressed via circulating thyroid hormone. An unexpected north to south increase in serum free thyroxine (FT4) and total 3, 5, 3′-triiodo-L-thyronine (T3) ( p < 0.02) correlated negatively with previously published BMR measurements. The increases in serum FT4 and T3 were symmetrical, so that the T3:FT4 ratio – interpretable as an index of conversion of T4 to T3 in nonthyroidal tissues – did not support relative decrease in production of T3 as a contributor to BMR. Increased north-to-south serum FT4 and T3 levels also correlated negatively with hemoglobin/hematocrit. North-to-south adaptations in spalacids include decreased BMR and hematocrit/hemoglobin in the face of increasing thyroid hormone levels, arguing for independent control of hormone secretion and BMR/hematocrit/hemoglobin. But the significant inverse relationship between thyroid hormone levels and BMR/hematocrit/hemoglobin is also consistent with a degree of cellular resistance to thyroid hormone action that protects against hormone-induced increase in oxygen consumption in a hostile, hypoxic environment.